Klasifikasi Tutupan Lahan di Kabupaten Trenggalek Menggunakan Google Earth Engine - Juan Vincent Elfonda; Vikhory Bagus Wahyu Nugroho; Tuhu Agung Rachmanto (Jurnal Kendali Teknik dan Sains, 2024)
Land cover is defined as the physical and biological cover of the earth's surface, both those formed naturally such as swamps, hills and rivers and those formed by man-made means such as rice fields, gardens, forests and buildings. As technology develops, conventional methods of satellite image processing are starting to be abandoned. This is because conventional methods require quite a long time to process satellite image data. The presence of Google Earth Engine (GEE), which is a cloud computing-based platform, makes it easier for users to process satellite image data boldly and for free. This research aims to classify satellite image land cover in the Trenggalek Regency area, East Java. The level of accuracy in this study uses a confusion matrix. The accuracy test results show a value of 90.23%.